ANALISIS KINERJA KEUANGAN PADA PT. HANJAYA MANDALA SAMPOERNA Tbk. - Nimiangge, Rona Rosy; Sabijono, Harijanto; Gamaliel, Hendrik (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
Development in technology that happen continuously have made the skills in financial analysis are more needed. Financial statement are the information source for financial position and company financial ferformance analysis.Evaluation of company financial performance in this researchÂ  using activity ratio and profitability ratio. This research using PT. Hanjaya Mandala Sampoerna Tbk as objek, this decision are based as 1 of 4 big company in cigarettes industry in Indonesia. The summary problemÂ  in this research is,â How the financial performanceat PT. Hanjaya Mandala Sampoerna Tbk. Based on activity ratio and profitability ratio for year 2015 and 2016?â The activity ratios are calculated with account receivable Turn Over,Inventory Turn Over, Total Asset Turn over,Otherwise Profitability Ratio are calculated with Gross profitÂ  Margin, Operating Profit Margin, and Net Profit Margin. The results showed that the ratios of poor activity were seen from the decline in value in the period 2015-2016, while the profitability ratios increased in the period 2015- 2016 which indicates the companys ability to generate profits has increased.Keywords : Financial Performance Analysis, Activity, Profitability